Appearance of the ν(Feiv=O) vibration from a ferry1-oxo intermediate in the cytochrome oxidase/dioxygen reaction - Babcock, Gerald; Varotsis, Constantinos (My University, 1990)
Time-resolved resonance Raman spectra have been recorded during the reaction of fully reduced (a2+a32+) cytochrome oxidase with dioxygen at room temperature. In the spectrum recorded at 800 μs subsequent to carbon monoxide photolysis, a mode is observed at 790 cm-1 that shifts to 755 cm-1 when the experiment is repeated with 18O2. The frequency of this vibration and the magnitude of the 18O2 isotopic frequency shift lead us to assign the 790-cm-1 mode to the FeIV=O stretching vibration of a ferryl-oxo cytochrome a3 intermediate that occurs in the reaction of fully reduced cytochrome oxidase with dioxygen. The appearance and vibrational frequency of this mode were not affected when D2O was used as a solvent. This result suggests that the ferryl-oxo intermediate is not hydrogen bonded. We have also recorded Raman spectra in the high-frequency (1000-1700 cm-1) region during the oxidase/O2 reaction that show that the oxidation of cytochrome a2+ is biphasic. The faster phase is complete within 100 μs and is followed by a plateau region in which no further oxidation of cytochrome a occurs. The plateau persists to ∼ 500 μs and is followed by the second phase of oxidation. These results on the kinetics of the redox activity of cytochrome a are consistent with the branched pathway discussed by Hill et al. [Hill, B., Greenwood, C., & Nichols, P. (1986) Biochim. Biophys. Acta 853, 91-113] for the oxidation of reduced cytochrome oxidase by O2 at room temperature
Keywords: Cytochrome oxidase; Cytochromes; Oxygen; Carbon monoxide; Deuterium oxide; Iron; Enzymology; Myocardium; Animals